PENGARUH TINGKAT HUNIAN HOTEL, JUMLAH WISATAWAN, DAN JUMLAH OBJEK WISATA TERHADAP PENDAPATAN ASLI DAERAH (PAD) KOTA PADANG TAHUN 2003-2012 - Sari, Riri Yulia (Pendidikan Ekonomi, 2014)
To the effect this research is subject to be get level affecting empiric prove hotel dwelling, total tourist and wisatas object amount to Regions Original Income Moorland City. Type and data source utilize quantitative approaching with secondary data that as time seriess data with observing period 2003 2012. analisiss method that is utilized is analisis bifilar linear regression. Result observationaling to point out that, First : Hotel dwelling zoom having for dont signifikan to Region Original Income Moorland City with appreciative coefficient as big as 0,55, assess this coefficient not signifikan because t little computing of t table. Both of : Total tourist having for positive and signifikan to Regions Original Income Moorland City with appreciative coefficient as big as 0,399, assess this coefficient signifikan because t computing outgrows of t table. Third : Total wisatas object having for positive and signifikan to Regions Original Income Moorland City with coefficient point as big as 2339,917, assess this coefficient signifikan because t computing outgrows of t table. Fourth : Point tests f as big as 107,166 by level signifikan 0,00, this signifikans point lies far under 0,05 so concluded that variable third signifikans ascendant to Regions Original Income Moorland City. Assess determinant coefficient (R 2 ) pointing out point r 2 ( R square ) as big as 0,98, it means 98% predict Region Original Incomes can third word independent variables, Meanwhile its rest 2% regarded by unanalyzed other variable.